Apakah yang Cape Town Perlu Katakan pada [Kaum Injili di] Indonesia?: Suatu Tinjauan dan Refleksi terhadap Komitmen Cape Town dan Implikasinya pada Kaum Injili di Indonesia - Adrianus Yosia (Veritas : Jurnal Teologi dan Pelayanan, 2017)
The Cape Town Commitment is one of the important documents pertaining to the history of evangelicals today. Even though this document is important rarely is it discussed in the Indonesia context. Thus, this article will discuss the Cape Town Commitment within two social contexts in Indonesia; multiculturalism and the multicultural condition and with respect to the evident poverty and economic gap. This study results in ten specific suggestions (in both the indicative and the imperative) that can function as guidelines for evangelicals in the Indonesia context.